Nursing Interventions for Patients with Anxiety Over Laboratory Testing an Integrated Psychological and Clinical Approach - Alotaibi, Falah; Alharbi, Mona Salem; Alshedokhi, Thamer Fahad; Almansour, Fahad Abdullah; Al-Dosari, Afaf Abdullah; Muslih, Maha Mohammed Bin; Alharbi, Wejdan Salem Furij; Alhawsawi, Bashair Hussein; Alameri, Fatemah Mohammed Salh; Alharbi, Mona Salem; Kabi, Khalid Mohammed Hassan (Journal of Ecohumanism, 2024)
Anxiety associated with laboratory testing is a common and often underrecognized issue that patients face, resulting in emotional distress and, in some cases, delays in testing and treatment. Managing this anxiety is critical to ensuring that patients undergo necessary medical procedures without added stress, which can negatively impact both the patient’s physical and mental health. This review aims to explore nursing interventions specifically designed to address anxiety in patients undergoing laboratory testing, with a focus on an integrated approach that combines psychological and clinical strategies. The collaboration between psychiatric consultants, nurse specialists, and laboratory technicians is paramount in providing comprehensive care. This article highlights key interventions, including cognitive-behavioral therapy (CBT), relaxation techniques, patient education, and psychosocial support, that can be employed to reduce anxiety. In addition, the review emphasizes the essential role of effective communication and pre-test education in calming anxious patients. The integration of these techniques within a multidisciplinary framework ensures a more holistic approach to anxiety management. Through this collaboration, healthcare providers can create a supportive environment, helping patients feel more informed and emotionally secure during laboratory procedures. The findings suggest that the combined efforts of psychiatric consultants, nurse specialists, and laboratory technicians significantly reduce anxiety, increase patient compliance with necessary testing, and ultimately improve patient outcomes.